Boys online/boys offline : seksuele dienstverlening door jongens/mannen (MSM) in Den Haag, 2009 - Van Gelder, Paul; van Lier, Léon (Den Haag : De Graaff, 2011)
Fonds Suzan Daniel (FSD)
Nederlands
Monografie